Peran Jaminan Kredit dalam Kasus Sengketa Nasabah dengan BCA: Kontroversi Eksekusi Lelang Sertifikat Persil Wilis sebagai Jaminan Kredit - Az-Zahra, Fatimah; Wulandari, Hania; Yesica S, Shely; Steffanie, Josephine; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
Credit collateral is a crucial aspect of loan agreements between banks and customers to ensure the certainty of debt repayment. However, the execution of collateral often triggers legal disputes, especially when customers feel disadvantaged. This journal examines the role of credit collateral in dispute cases between customers and PT Bank Central Asia (BCA), focusing on the controversy surrounding the auction execution of the Persil Wilis certificate as credit collateral. Using a normative juridical approach, this study analyzes the legal basis and execution procedures of credit collateral conducted by BCA, including compliance with banking regulations and legal protection for customers. The research findings indicate that although banks have the right to execute credit collateral through auctions, issues related to transparency, procedures, and customer rights often arise, potentially leading to legal claims. This case reflects the imbalance of power between banks and customers in banking practices and highlights the need for stronger regulations to prevent the misuse of execution rights by creditors. Therefore, this study recommends enhanced supervision of the credit collateral auction process, increased transparency in providing information to customers, and stronger legal protection to ensure fairness in resolving banking disputes.